Global trends in research on irritable bowel syndrome and the brain–gut axis: Bibliometrics and visualization analysis - Wu, Peng-Ning; Xiong, Shuai; Zhong, Peng; Yang, Wan-Qing; Chen, Min; Tang, Tai-Chun (Frontiers in Pharmacology, 2022)
Irritable bowel syndrome (IBS) is a gastrointestinal disorder with no structural damage, and its pathogenesis remains unclear. Studies have shown that the brain-gut axis is closely related to the occurrence of IBS. However, studies of IBS related to brain-gut axis have not been systematically analyzed by bibliometrics and visual analysis. This study is based on 631 publications of Web of Science Core Collection (WoSCC) to analyze hot spots and trends in this field. The collaborations between different authors, institutions, countries, and keywords were bibliometric analysed by CiteSpace software. Meanwhile, VOSviewer analyzed the references. The results show that since 2012, the number of publications has been growing rapidly. According to the collaborative network analysis, the United States, the National University of Ireland, Cork and J F Cryan are the countries, institutions and authors contributing the most, respectively. Through keywords and literature analysis, mechanism and therapy associated with IBS and brain gut axis is still a research focus in recent years. Furthermore, the physiological and pathological mechanism of brain-gut axis influencing IBS (related to gastrointestinal dysfunction, vagus nerve, visceral pain, intestinal flora, serotonin, tryptophan metabolism, stress, brain derived neurotrophic factor(BDNF), malonyldialdehyde), is the future research trend, especially the mechanisms related to intestinal flora. This is the first bibliometric and visualization analysis of IBS and brain-gut axis related literature to explore research hotspots and trends.